ANALISIS PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, DAN STRES KERJA TERHADAP INTENTION TO QUIT (Studi Pada Karyawan PT Bank Jateng) - Putradiarta, Alfian Arya; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2016)
Turnover is one of the serious problems that often occur in a company. There are still many companies that have problems regarding the high level turnover that one of them is PT Bank Jateng. This study aims to examine and analyze the effects of job satisfaction, organizational commitment, and job stress on intention to quit in PT Bank Jateng.Data collection methods which used in this study was a questionnaire with sample of 80 PT Bank jateng employees using stratified sampling method. This study used mutliple linear regression analysis.The result of this study showed that the variables of job satisfaction and organizational commitment had significant and positively effect on intention to quit while job stress affect the intention to quit significant and negatively. These variables influence amounted to 43,9% of the intention to quit. The remaining 56,1% is influenced by variables outside of this study.